Trigger finger and carpal tunnel syndrome: a meta-analysis of co-occurrence and risk - Péter Sallai; Barbara Sebők; Luca Hergár; Judit Réka Hetthéssy (Journal of Plastic Surgery and Hand Surgery)
Carpal tunnel syndrome (CTS) and trigger finger (TF) are two of the most common conditions of the hand. Co-occurrence is mentioned by a number of publications, but there are few high-level evidence studies that summarise the results of large databases to quantify the chances of concurrency in detail making it difficult to gauge clinical significance. We aimed to quantify the impact of CTS, TF and surgery for these conditions on the prevalence of the other condition. Systematic review based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, with registration in the PROSPERO database. TF is clearly more common with CTS and after CTS surgery, so it is important to seek out symptoms of TF, even the initial ones, at every examination performed for CTS. Thus, conservative treatment of TF maybe started in time and TF surgery may be performed in conjunction with CTS surgery. Level of Evidence: IV. Prospero registration number: CRD42022382672